MODIFIKASI COAL FEEDER DAN COAL THROWER UNIT #1 DI PLTU HOLTEKAMP 2 X 10 MW - Solichin, Ahmad; Gunawan, Gunawan (Elektrika, 2026)
The combustion system in a coal-fired boiler is greatly influenced by the performance of the coal supply and distribution equipment, especially the coal feeder and coal thrower. Problems that often occur include uneven (unstable) coal distribution, increased fuel consumption and low combustion efficiency. This study aims to modify the coal feeder and coal thrower system to equalize fuel distribution, fuel efficiency and improve the stability of coal supply in the boiler combustion chamber at the Holtekamp 2 x 10 MW PLTU. The method here uses qualitative and quantitative methods to obtain appropriate data before and after the modification of the coal feeder - coal thrower overhaul unit #1. Modifications are made by adding coal feeders to each coal thrower so that each line can be controlled to optimize the distribution and evenness of coal and can be calculated to obtain SFC and auxiliary power values. The implementation results show an increase in coal flow stability, more even combustion, reduced coal combustion residue and increased boiler thermal efficiency. The lowest SFC value occurred in September at 1,440 kg/kWh, with an average load of 7.45 MW. Meanwhile, the auxiliary power value reached 8,807 kW (Coal Feeder) and 7,741 kW (Coal Thrower) in November, reaching 7,574 MW during the performance test. Keywords: Coal Feeder, Coal Thrower, Distribution, Efficiency, Modification ABSTRAK Sistem pembakaran pada boiler berbahan bakar batu bara sangat dipengaruhi oleh kinerja peralatan penyuplai dan penyebar batu bara, khususnya coal feeder dan coal thrower. Permasalahan yang sering terjadi meliputi distribusi batu bara yang tidak merata (tidak stabil), peningkatan konsumsi bahan bakar dan efisiensi pembakaran yang rendah. Hal ini bertujuan untuk melakukan modifikasi pada sistem coal feeder dan coal thrower untuk pemerataan distribusi bahan bakar, efisiensi pemakaian bahan bakar dan meningkatkan kestabilan suplai batu bara di dalam ruang bakar boiler di PLTU Holtekamp 2 x 10 MW. Metode disini menggunakan cara kualitatif dan kuantitatif untuk mendapatkan data yang sesuai before – after modifikasi coal feeder - coal thrower overhaul unit #1. Modifikasi dilakukan dengan cara menambahkan coal feeder pada masing - masing coal thrower agar nantinya dapat dikontrol setiap line nya untuk mengoptimalkan penyebaran dan pemerataan batu bara serta dapat dilakukan perhitungan untuk mendapatkan nilai SFC dan auxiliary power. Hasil implementasi menunjukkan adanya peningkatan kestabilan aliran batubara, pembakaran yang lebih merata, penurunan sisa pembakaran batu bara dan peningkatan efisiensi termal boiler. Untuk nilai SFC terendah terjadi pada bulan september sebesar 1,440 Kg/kWh dan rata – rata beban sebesar 7,45 MW. Disisi lain, nilai Auxiliary Power terjadi pada bulan november sebesar 8,807 kW (Coal Feeder) dan 7,741 kW (Coal Thrower) dan saat performance test sebesar 7,574 MW.